Implementasi BUMDes dalam Upaya Menciptakan Lapangan Kerja bagi Pemuda di Desa Jungjang - Rachman Yushril Fadillah; Mintarsih Arbarini (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2022)
This study aims to (1) describe the programs held by BUMDes, (2) describe the implementation of the BUMDes District program in an effort to create employment opportunities for youth, (3) describe the obstacles and solutions that have been carried out while running the BUMDes District program. This research approach uses a qualitative case study. The research was conducted in Desa Jungjang, Kecamatan Arjawinangun, Kabupaten Cirebon. The research subjects were 7 people, consisting of 2 BUMDes implementers and 5 youths. There were 2 research informants, the Head of Hamlet V and the Village Secretary. Data collection techniques using observation, interviews, and documentation. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and making conclusions. The validity of the data was tested using source triangulation and technical triangulation. The results of the study show (1) the programs organized by BUMDes Jungjang aim to improve the living standards of rural communities, (2) the implementation of the BUMDes District program in the form of a village business area that provides employment through empowerment of prospective workers, (3) implementation barriers include limited information dissemination. , empowerment activities are monotonous, and teaching materials do not match the abilities of participants, while the solutions implemented include instructing participants to disseminate information, holding empowerment activities in an informal, and bringing a professional educator.